2016
DOI: 10.1002/jcb.25605
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Drug Targets

Abstract: Transcription factors represent the point of convergence of multiple signaling pathways within eukaryotic cells. Deregulated transcription factors contribute to the pathogenesis of a plethora of human diseases, ranging from diabetes, inflammatory disorders and cardiovascular disease to many cancers, and thus these proteins hold great therapeutic potential. Direct modulation of transcription factor function by small molecules is no longer regarded a Sisyphean task, as recent work in drug discovery has revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 48 publications
0
71
0
Order By: Relevance
“…17,18 Transcription factors are protein molecules that can specifically bind to upstream of the 5ʹ end of the gene, thereby ensuring target gene expression with a specific intensity. 19 TCF1 is expressed in multiple isoforms. All isoforms of TCF1 share the common HDAC and DNA binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Transcription factors are protein molecules that can specifically bind to upstream of the 5ʹ end of the gene, thereby ensuring target gene expression with a specific intensity. 19 TCF1 is expressed in multiple isoforms. All isoforms of TCF1 share the common HDAC and DNA binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…TFs represent the key point of convergence of multiple signaling pathways in cells and play critical roles in tumorigenesis and cancer progression because TFs can regulate comprehensive transcription alterations in cancer cells. [ 3–5 ] Sp4 is a general TF that binds to and acts through GC base boxes, which are frequently occurring DNA elements present in many promoters and enhancers. [ 14 ] We found that SRSP promoted the inclusion of exon 3 of TF Sp4 to promote long Sp4 splicing variant formation (we termed L‐Sp4) and suppress short Sp4 splicing variant formation without exon 3 (we termed S‐Sp4) ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated that TFs account for 20% of oncogenes in cancer. [ 3–5 ] The classic examples include p53, Ets, AP‐1, c‐Myc, and NFκB. Alternations of TF activity underlie many human diseases including cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because transcription factors play central roles in the cell, mutations in these proteins can lead to aberrant gene regulation, which in turn, can lead to development of diseases [recently reviewed in Ref. ( ). Many transcription factors regulate cell survival and proliferation, and their dysregulation is often key to oncogenesis: for example, the MYC transcription factor is involved in numerous normal cellular processes, but in deregulated and overexpressed form, MYC is involved in over half of all human cancers [see Ref.…”
Section: Introductionmentioning
confidence: 99%